ANALISIS TINGKAT KEMATANGAN BUAH SAWIT DENGAN INJEKSI TEGANGAN SEARAH - Dino Yanuardi; Saktioto Saktioto; Romi Fadli Syahputra; Defrianto Defrianto; Yan Soerbakti (Komunikasi Fisika Indonesia, 2023)
Palm fruit is Indonesia's main communiqué as the largest foreign exchange contributor processed into crude palm oil (CPO). However, the quality of CPO that will be produced is influenced by the right level of maturity of palm fruit so as not to cause losses from the processor. Losses from the palm fruit processing can be overcome using a method that can determine the maturity level of the palm fruit, one of which is by injecting the voltage in the direction of the palm fruit. The purpose of direct voltage objection to the function of time in the palm fruit is to obtain a voltage response relationship to the content of yield, moisture content and free fatty acid (ALB) in the palm fruit. In this study, palm fruit was classified into 4 levels of maturity, namely unripe, almost ripe, ripe and overripe given direct voltage injection of 9 Volts for 1 minute with 3 repetitions using four electrodes arranged parallel to obtain an electrical voltage response with an electrode diameter of 1.4 mm. The distance between electrodes was chosen to be 4 – 6 mm from stainless steel materials, and the depth of the electrode to the palm fruit is 3 – 5 mm. Palm fruit was injected with electrical voltage and obtained the value of voltage response, electric current, resistivity and power of each level of maturity. The electrical information obtained will explain the yield content, water content and ALB in palm fruit in accordance with the classification of ripeness. The results of the study obtained, that the palm fruit is said to ripen when it has a voltage response value of 0.586 – 0.765 V, electric current 385 – 404.9 μA, resistivity 40.197 – 54.523 Ωm, and power 0.238 – 0.299 mW. The results showed that the maturity level of palm fruit based on its chemical content affects the properties of electricity.